2022
DOI: 10.3390/plants11152071
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mammalian Sex Hormones on Polymorphism and Genomic Instability in the Common Bean (Phaseolus vulgaris L.)

Abstract: Mammalian sex hormones are steroid-structured compounds that support the growth and development of plants at low concentrations. Since they affect the physiological processes in plants, it has been thought that mammalian sex hormones may cause modifications to plant genomes and epigenetics. This study aims to determine whether different mammalian sex hormones (17 β-estradiol, estrogen, progesterone, and testosterone) in several concentrations (0, 10−4, 10−6, and 10−8 mM) affect genetic or epigenetic levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The concentration and quality of genomic DNA were measured with a Nanodrop spectrophotometer (Qiagen Qiaxpert, Qiagen, Hilden, Germany) (Thermo Fisher Scientific, Waltham, MA, USA) and run on 1.5% (w/v) agarose gel. Twenty primers were tested for iPBS-PCR amplification [65]. For iPBS analysis, a PCR reaction was carried out by Hosseinpour et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…The concentration and quality of genomic DNA were measured with a Nanodrop spectrophotometer (Qiagen Qiaxpert, Qiagen, Hilden, Germany) (Thermo Fisher Scientific, Waltham, MA, USA) and run on 1.5% (w/v) agarose gel. Twenty primers were tested for iPBS-PCR amplification [65]. For iPBS analysis, a PCR reaction was carried out by Hosseinpour et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…Their physiological activity, genomic DNA instability, and epigenetic effects on plants have not yet been completely described, despite the fact that the amounts, receptors, and individual binding sites of MSHs in plants have been partially revealed [12]. Mammalian sex hormones can induce molecular changes by affecting genome stability and epigenetic mechanisms [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that plants are able to maintain their survival cycle by exploiting changes in response to conditions in their environment [17]. In particular, there is evidence of substantial connections between hormones produced by plants and epigenetic signals produced by the plants [13,18]. The study of epigenetic changes can be approached from many different angles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of sex hormones greatly increased the proline and antioxidant enzyme activity in vitro cultured triticale mature embryos (Uysal and Bezirganoğlu, 2017). Responses of in vitro cultured wheat and bean plants to different types and concentrations of sex hormones varied signi cantly and differences were attributed to epigenetic modi cations (Türkoğlu 2022a(Türkoğlu , 2022b. Latter reports revealed that there is signi cant interaction between sex hormone type by concentration.…”
Section: Introductionmentioning
confidence: 99%